Non-dipping circadian pattern as a predictor of incipient nephropathy in normotensive normoalbuminuric type 1 diabetics - Jorge da Silva Franco, Roberto [UNESP]; Antonio Vieira Filho, José [UNESP]; Inomata Cardoso da Silva, Douglas [UNESP]; Cuadrado Martin, Luis [UNESP]; Alves Silva, Bruno [UNESP]; Garcia Zanati Bazan, Silméia [UNESP]; Barretti, Pasqual [UNESP]; Regina Nogueira, Célia [UNESP] (Taylor & Francis, 2023)
The objective of this study was to assess the value of the abnormal circadian blood pressure pattern by ambulatory blood pressure monitoring (ABPM) to predict the onset of abnormal albuminuria in normotensive and normoalbuminuric DM1 patients. The participators were submitted to ABPM and followed prospectively until the onset of albuminuria or the end of follow-up. The patients with normal circadian blood pressure pattern were compared with the non-dippers in regard of the time interval free of albuminuria. The survival curves were evaluated by the Kaplan–Meier method. Of 34 patients screened, 10 patients matched the exclusion criteria. Therefore, 24 patients were submitted to ABPM, aged 24 ± 8.3 y, 18 men, and all Caucasian. Elevated levels of albuminuria did not occurin any individual with normal systolic blood pressure dip (>10%) at 54 months of follow-up. Only 22% of patients among non-dippers were free of albuminuria (<30 mg/g maintained for 3 months) at the same time (p = 0.049). Patients that reached the outcome were homogeneous in regard to other clinical and ABPM data evaluated. Abnormal systolic blood pressure circadian pattern predicts the evolution to incipient nephropathy in normotensive normoalbuminuric DM1 patients.
Keywords: Albuminuria; ambulatory blood pressure monitoring; blood pressure circadian rhythm; diabetes mellitus; diabetic nephropathy